44.8k views
3 votes
t2 + 2t + 1 = 0 Solve using the quadratic formulaWrite your answers as integers, proper or improper fractions in simplest form, or decimals rounded to the nearest hundredth.

User Zeno Rocha
by
6.2k points

2 Answers

1 vote
t²+ 2t + 1 = 0

a=1, b=2 & c=1 The formula is x'=[-b+√(b²-4ac)]/(2a)

and====================>x"=[-b-√(b²-4ac)]/(2a)

x' = [-2+√(2²-4(1)] / 2(1) ===> x' = -2/2 ==> x' =-1 & x" = -1
x'=x"= -1
User Idriys
by
6.1k points
4 votes
t=-1 hope i helped im sure it is right
User Neil Williams
by
5.9k points